Spatial and temporal concentration of tourism supply and demand in Northern Portugal. Application of the Herfindahl-Hirschman index - Fernandes, Paula Odete (2019)
The northern region of Portugal, in the last years, has experienced the enhancement of tourism demand, which may induce the emergence of an over tourism phenomenon in some particular subregions of the North of Portugal. This phenomenon may cause significant destruction of the living conditions of residents, landscapes, seascapes, air and water quality, causing economic inequalities and social exclusion. The aim of this research paper is to understand if the phenomena of over tourism is present in the North of Portugal and if it changed overtime. The concentration of tourism activity in different municipality subregions can be measured with the Herfindahl-Hirschman Index a well know economic concentration measure. Using as variables the number guest and their expenditure in accommodation, to measure the demand, and the number of establishments, bedrooms and lodging capacity to measure the supply was possible to follow the concentration of tourism demand and supply in the 8 NUTIII regions located in the North of Portugal. The results showed that a specific subregion–Area Metropolitan do Porto–concentrates both the tourism demand and supply in the years 2014 and 2017, despite the increasing values found for all the variables in the 8 subregions. When it is observed a decrease in the levels of concentration are the subregions near by the most concentrate one that increase the share of tourism demand and supply. More rural and less populated areas need more targeted and specific policies measures to attract even more visitors.